The acute and sub-chronic effects of cocoa flavanols on mood, cognitive and cardiovascular health in young healthy adults: a randomized, controlled trial - Massee, Laura A.; Ried, Karin; Pase, Matthew; Travica, Nikolaj; Yoganathan, Jaesshanth; Scholey, Andrew; Macpherson, Helen; Kennedy, Greg; Sali, Avni; Pipingas, Andrew (Frontiers in Pharmacology, 2015)
Cocoa supplementation has been associated with benefits to cardiovascular health. However, cocoa’s effects on cognition are less clear. A randomized, placebo-controlled, double-blind clinical trial (n=40, age M= 24.13 years, SD = 4.47 years) was conducted to investigate the effects of both acute (same-day) and sub-chronic (daily for four-weeks) 250mg cocoa supplementation on mood and mental fatigue, cognitive performance and cardiovascular functioning in young, healthy adults. Assessment involved repeated 10-minute cycles of the Cognitive Demand Battery (CDB) encompassing two serial subtraction tasks (Serial Threes and Sevens), a Rapid Visual Information Processing task, and a mental fatigue scale over the course of half an hour. The Swinburne University Computerised Cognitive Assessment Battery (SUCCAB) was also completed to evaluate cognition. Cardiovascular function included measuring both peripheral and central blood pressure and cerebral blood flow. At the acute time point, consumption of cocoa significantly improved self-reported mental fatigue and performance on the Serial Sevens task in cycle one of the CDB. No other significant effects were found. This trial was registered with the Australian and New Zealand Clinical Trial Registry (Trial ID: ACTRN12613000626763). Accessible via http://www.anzctr.org.au/TrialSearch.aspx?searchTxt=ACTRN126130006 26763&ddlSearch=Registered